Preventing Foodborne Illness: Norovirus - Keith R. Schneider; Renée M. Goodrich-Schneider; Mike Hubbard; Rajya Shukla (EDIS)
Revised! FSHN-05-18, a 4-page fact sheet by Keith R. Schneider, Renée Goodrich Schneider, Mike Hubbard, and Riya Shukla, provides essential information about noroviruses in a question-and-answer format. Includes references. Published by the UF Department of Food Science and Human Nutrition, April 2009.